2012
DOI: 10.1186/1475-2859-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Biomass pretreatment affects Ustilago maydis in producing itaconic acid

Abstract: BackgroundIn the last years, the biotechnological production of platform chemicals for fuel components has become a major focus of interest. Although ligno-cellulosic material is considered as suitable feedstock, the almost inevitable pretreatment of this recalcitrant material may interfere with the subsequent fermentation steps. In this study, the fungus Ustilago maydis was used to produce itaconic acid as platform chemical for the synthesis of potential biofuels such as 3-methyltetrahydrofuran. No studies, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
129
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 40 publications
10
129
2
1
Order By: Relevance
“…Cytosolic ATP-Citrate lyase is necessary to recover the Acetyl CoA in the cytosol for use in lipid synthesis, and U. maydis must use this route due to the presence of an ATP-Citrate lyase gene (UM 01005.1) [26] [27]. During the production of itaconic acid (methylene succinic acid) in U. mayids during nitrogen-limited conditions, it has been suggested that the relative oxygen content decreased, making the biomass more reduced and allowing for the accumulation of less oxygenated compounds as hydrocabons [28]. These authors also included in their study the influence of nitrogen supply and found that nitrogen limitation increased the cell size, probably due to the accumulation of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic ATP-Citrate lyase is necessary to recover the Acetyl CoA in the cytosol for use in lipid synthesis, and U. maydis must use this route due to the presence of an ATP-Citrate lyase gene (UM 01005.1) [26] [27]. During the production of itaconic acid (methylene succinic acid) in U. mayids during nitrogen-limited conditions, it has been suggested that the relative oxygen content decreased, making the biomass more reduced and allowing for the accumulation of less oxygenated compounds as hydrocabons [28]. These authors also included in their study the influence of nitrogen supply and found that nitrogen limitation increased the cell size, probably due to the accumulation of lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous molecular tools have been developed over the last few years, including resistance markers, protein tags (39), and efficient strain generation by Golden Gate cloning (40). In addition, in bioreactors, the fungus confers a remarkably high resistance to shearing forces and to impurities in the fermentation broth, like those observed after biomass pretreatment (26,41). The largescale cultivation in bioreactors is well established, for instance, for the closely related fungus Pseudozyma tsukubaensis (42).…”
mentioning
confidence: 99%
“…Xylitol, a sweetener, was produced from xylose by Candida guilliermondii [17], while Saccharomyces cerevisae [54] and Clostridium beijerinckii [55] convert sugars to ethanol and butanol, respectively-second generation biofuels. Itaconic acid, a building block for fibers and rubbers, was produced by Ustilago maydis from xylose or glucose [18] and hydrogen, a third generation biofuel, is obtained from sugars with the use of Caldicellulosiruptor saccharolyticus [16]. However, the presence of three major polymers and other minor substances in lignocellulose, their rigidity and strong structure make the access to valuable carbohydrates very complicated.…”
Section: Composition and Treatment Of Lignocellulose Materialsmentioning
confidence: 99%
“…The ability of microalgae to grow on organic substrates raises the possibility of cultivating microalgae on lignocellulose feedstock and thus reduce cultivation costs and increase productivity. Lignocellulose is the world's most abundantly available raw plant material that can become a promising feedstock for microorganisms such as bacteria, yeasts and fungi to produce high value added products and biofuels [16][17][18]. Energies 2014, 7…”
mentioning
confidence: 99%
See 1 more Smart Citation